Moral Legitimacy: The Struggle Of Homeopathy in the NHS - Crawford, Louise (Bioethics, 2016)
This article deploys a well-established theoretical model from the accountability literature to the domain of bioethics. Specifically, homeopathy is identified as a controversial industry and the strategic action of advocates to secure moral legitimacy and attract public funding is explored. The Glasgow Homeopathic Hospital (GHH) is used as the location to examine legitimizing strategies, from gaining legitimacy as a National Health Service (NHS) hospital in 1948, followed by maintaining and repairing legitimacy in response to government enquires in 2000 and 2010. An analysis of legitimizing strategies leads to the conclusion that advocates have been unsuccessful in maintaining and repairing moral legitimacy for homeopathy, thus threatening continued public funding for this unscientific medical modality. This is an encouraging development towards open and transparent NHS accountability for targeting limited public resources in pursuit of maximizing society's health and well-being. Policy implications and areas for future research are suggested.